PRODUCTIVE WAQF AND MSME EMPOWERMENT: A SYSTEMATIC LITERATURE REVIEW ON MODELS, IMPACTS, AND IMPLEMENTATION CHALLENGES - Ahmad Eko Saputro (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
Productive waqf has emerged as a strategic Islamic social finance instrument with significant potential to support sustainable economic development, particularly through the empowerment of Micro, Small, and Medium Enterprises (MSMEs). Despite growing scholarly attention, existing studies remain fragmented and context-specific, lacking a comprehensive synthesis of productive waqf models, their empowerment outcomes, and implementation challenges. This study addresses this gap by providing an integrated and up-to-date review of productive waqf literature related to MSME empowerment. The research aims to identify dominant productive waqf models, analyze their impacts on MSMEs, and examine key implementation challenges. Employing a Systematic Literature Review (SLR) approach based on the PRISMA framework, this study reviews 15 peer-reviewed journal articles published between 2020 and 2025. The findings reveal that asset-based productive waqf models dominate the literature (60%), while cash- and financial-based models account for 40%. Productive waqf contributes positively to MSME development by enhancing access to capital, strengthening business capabilities, and fostering income growth, employment generation, and business sustainability. However, regulatory fragmentation, limited waqf literacy, and inadequate managerial capacity continue to hinder its effective implementation